The cinematic political : film composition as political theory - Shapiro, Michael J. (New York : Routledge, 2020)
"In this book, Michael J. Shapiro stages a series of pedagogical encounters between political theory, represented as a compositional challenge, and cinematic texts, emphasizing how to achieve an effective research paper/essay by heeding the compositional strategies of films. The text's distinctiveness is its focus on the intermediation between two textual genres. It is aimed at providing both a conceptual introduction to the politics of aesthetics and a guide to writing strategies. In its illustrations of encounters between political theory and cinema, the book's critical edge is its emphasis on how to intervene in cinematic texts with innovative conceptual frames in ways that challenge dominant understandings of life worlds. The Cinematic Political is designed as a teaching resource that introduces students to the relationship between film form and political thinking. With diverse illustrative investigations, the book instructs students on how to watch films with an eye toward writing a research paper in which a film (or set of films) constitutes the textual vehicle for political theorizing"--
Engaging Lars von Trier's the element of crime -- Toward a politics of now-time: reading Hoop Dreams with Kubrick's Barry Lyndon -- "Hiroshima" -- "The light of reason" -- "Borderline justice" -- A bi-city cinematic experience -- The phenomenology of the cinema experience.
Includes bibliographical references and indexes.
Keywords: Motion pictures -- Political aspects; Motion pictures -- Aesthetics; Aesthetics -- Political aspects; English language -- Rhetoric; Report writing